Thiazolidine derivatives as potent and selective inhibitors of the PIM kinase family. Issue 9 (1st May 2017) - Bataille, Carole J.R.; Brennan, Méabh B.; Byrne, Simon; Davies, Stephen G.; Durbin, Matthew; Fedorov, Oleg; Huber, Kilian V.M.; Jones, Alan M.; Knapp, Stefan; Liu, Gu; Nadali, Anna; Quevedo, Camilo E.; et al.
Graphical abstract: Abstract: The PIM family of serine/threonine kinases have become an attractive target for anti-cancer drug development, particularly for certain hematological malignancies. Here, we describe the discovery of a series of inhibitors of the PIM kinase family using a high throughput screening strategy. Through a combination of molecular modeling and optimization studies, the intrinsic potencies and molecular properties of this series of compounds was significantly improved. An excellent pan-PIM isoform inhibition profile was observed across the series, while optimized examples show good selectivity over other kinases. Two PIM-expressing leukemic cancer cell lines, MV4-11 and K562, were employed to evaluate the in vitro anti-proliferative effects of selected inhibitors. Encouraging activities were observed for many examples, with the best example (44 ) giving an IC50 of 0.75 μM against the K562 cell line. These data provide a promising starting point for further development of this series as a new cancer therapy through PIM kinase inhibition.